Magnetospheric response to magnetosheath pressure pulses: A low pass filter effect - Archer,MO; Horbury,TS; Eastwood,JP; Weygand,JM; Yeoman,TK (Journal of Geophysical Research, 2013)
Abstract. We present observations from the magnetopause to the ground during periods of large amplitude, transient dynamic pressure pulses in the magnetosheath. While individual magnetosheath pulses are sharp and impulsive, the magnetospheric response is much smoother with frequencies in the Pc5-6 range being excited in the compressional and poloidal components of the magnetic field. We show that the magnetopause acts like a low pass filter, suppressing timescales shorter than a few minutes. Further filtering appears to occur locally within the magnetosphere, which may be due to the unusual field line resonance frequency profile on this day. Ground magnetometer and radar data along with equivalent ionospheric currents show signatures of travelling convection vortices, similar to the response from pressure variations of solar wind origin. However, the signatures are associated with groups of magnetosheath pulses rather than individual ones due to the impulsive nature of the pressure variations. Thus the scale-dependent magnetospheric response to these transient pressure variations, results in coherent signatures on longer timescales than any individual pulse.